Inappropriate cleaning treatments of stainless steel AISI 316L caused a corrosion failure of a liquid transporter truck. (November 2020) - Romanovski, Valentin; Frantskevich, Vitali; Kazlouski, Vitali; Kasach, Aliaksandr; Paspelau, Andrei; Hedberg, Yolanda; Romanovskaia, Elena
Highlights: A corrosion failure of stainless steel 316L of a transport container investigated. A non-licensed acidic cleaning agent for removing latex residues has been used. The acidic cleaning agent contained chlorides and oxidative species. Cleaning with that agent and the transport of 90% acetic acid caused corrosion. Self-sustaining pitting corrosion under these conditions. Abstract: Corrosion of transport tanks for transporting aggressive liquids is undesirable from both economic, safety, and sustainability perspectives. It is thereby not only important to consider the composition of the aggressive liquids to be transported and the material of the tank, but also the composition of the cleaning liquids and procedures. Triggered by an industrial case, we investigated the extent of corrosion during cleaning treatments and simulated contact with transported fluids at relevant conditions. Corrosion of stainless steel AISI 316L was investigated in commercial latex remover liquid, 90 wt% acetic acid, two different car shampoos, and solution of potassium hydroxide at room temperature. After electrochemical, solution analytical, and surface analytical analysis of the transporter tank material and some of the transported and cleaning fluids, we found that even a short time of use of non-licensed latex remover liquid could trigger a self-sustaining mechanism for pitting corrosion of stainless steel AISI 316L.